Prawne aspekty wykorzystania wizerunku sportowca w świetle działań marketingowych = Legal aspects of athletes' image rights usage in the light of marketing activities - Westfal, Krzysztof M. (Journal of Education, Health and Sport, 2016)
Westfal Krzysztof M. Prawne aspekty wykorzystania wizerunku sportowca w świetle działań marketingowych = Legal aspects of athletes' image rights usage in the light of marketing activities. Journal of Education, Health and Sport. 2016;6(6):69-85. eISSN 2391-8306. DOI http://dx.doi.org/10.6084/m9.figshare.3410083 http://ojs.ukw.edu.pl/index.php/johs/article/view/3558 Original Text published © The Author (s) 2016. Westfal Krzysztof M. Prawne aspekty wykorzystania wizerunku sportowca w świetle działań marketingowych = Legal aspects of athletes' image rights usage in the light of marketing activities. Quality in Sport. 2016;2(2):80-96. eISSN 2450-3118. DOI http://dx.doi.org/10.5281/zenodo.53980 https://pbn.nauka.gov.pl/sedno-webapp/works/728308 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. Prawne aspekty wykorzystania wizerunku sportowca w świetle działań marketingowych Legal aspects of athletes' image rights usage in the light of marketing activities Krzysztof M. Westfal[1] Katedra Prawa Cywilnego i Handlowego Wydziału Prawa i Administracji Uniwersytet im. Adma Mickiewicza w Poznaniu Streszczenie Z reguły prawo nie nadąża za życiem. Potencjał ekonomiczny jaki niesie ze sobą wizerunek sportowca został dostrzeżony przez specjalistów marketingowych już wiele lat temu. Z tego tytułu gwiazdy zawodowego sportu osiągają każdego roku ogromne sumy. W praktyce gospodarczej i w realiach profesjonalnego sportu komercyjny wymiar wizerunku sportowca jest faktem. Także dające się zaobserwować tendencje rozwoju oraz wykładni polskiego prawa wydają się fakt ten zauważać. Podejmowane próby ujęcia majątkowego czy też mieszanego osobisto-majątkowego charakteru prawa do wizerunku zasługują na aprobatę. Doniosłość zagadnienia prawa do wizerunku profesjonalnych sportowców znalazła swoje odzwierciedlenie także na gruncie obowiązującego prawa. Art. 14 ust. 1-3Ustawy z dnia 25 czerwca 2010 roku o sporcie (Dz.U.2016.176 j.t.) wprowadzają bowiem przepisy szczególne w stosunku do art. 23 i 24 ust. 1-3 Ustawy z dnia 23 kwietnia 1964 r. Kodeks Cywilny (Dz.U.2016.380 j.t.) oraz art. 81 ust. 1 i 2 Ustawy z dnia 4 lutego 1994 r. o prawie autorskim i prawach pokrewnych (Dz.U.2006.90.631 j.t. z późn. zm.), które wyznaczają główne ramy prawne prawa do wizerunku. Wspomniane przepisy Ustawy o sporcie przyznają polskiemu związkowi sportowemu oraz Polskiemu Komitetowi Olimpijskiemu wyłączne prawo do wykorzystywania do swoich celów gospodarczych wizerunku, odpowiednio, członka kadry narodowej w stroju reprezentacji kraju albo członka reprezentacji olimpijskiej w stroju reprezentacji olimpijskiej z chwilą ich powołania do takiej reprezentacji. Szczególne rozwiązania prawne funkcjonujące w odniesieniu do wizerunku profesjonalnych sportowców były także przedmiotem orzecznictwa Sądu Najwyższego. Kluczowe znaczenie dla wykładni art. 14 ust. 1-3 Ustawy o sporcie ma wyrok SN z dnia 16 grudnia 2009 r., sygn. akt: I CSK 160/09, który wydany został w oparciu o nieobowiązujący już art. 33 ust. 1 i 2 uchylonej Ustawy z dnia 29 lipca 2005 r. o sporcie kwalifikowanym (Dz.U. 2005 nr 155 poz. 1298). Dla zagadnienia wykorzystania wizerunku sportowca nie bez znaczenia pozostaje także fakt, że profesjonalni sportowcy posiadają najczęściej także status osoby powszechnie znanej. W świetle art. 81 ust. 2 o.p.a.p.p. rozpowszechnianie wizerunku sportowca – osoby powszechnie znanej nie wymaga zgody takiej osoby, jeżeli wizerunek wykonano w związku z pełnieniem przez nią funkcji publicznych, a w szczególności społecznych lub zawodowych. W przypadku podmiotów uprawnionych do rozpowszechniania wizerunku sportowców panuje spora różnorodność. W zależności od sytuacji faktycznej uprawnienie takie przysługiwać może oprócz samego sportowca chociażby Polskiemu Komitetowi Olimpijskiemu, polskiemu związkowi sportowemu, klubowi sportowemu lub organizacji zbiorowego zarządzania prawami sportowców. Mając na względzie wielopłaszczyznowość problematyki wizerunku sportowca, oraz powszechność zawierania umów marketingowych, których przedmiotem jest właśnie wizerunek postulować należy, żeby dające się zaobserwować zmiany w prawym ujęciu tego zagadnienia zmierzały w kierunku sprostania potrzebom kreowanym przez rynek. Słowa kluczowe: prawo sportowe, prawo do wizerunku, prawo do wizerunek sportowca, komercjalizacja prawa do wizerunku, marketing w sporcie Summary Usually the law is at least one step behind the market demands. Economic potential of athletes’ image rights has been recognized by marketing specialists many years ago. Selling image rights brings huge amounts of money to professional athletes each year. In market practice and in the realities of professional sport, commercial character of the image rights has become a fact. Also noticeable tendencies in development of Polish law interpretation seems to acknowledge that fact. Latest attempts of redefining nature of the image rights as economical or mixed economical-personal one deserves for approval. The importance of the issue of professional athletes’ image has found its reflection in legislation. Art. 14 par. 1-3 of the Sports Act of 25th June 2010 sets lex specialis to art. 23 and 24 paragraphs 1-3 of the Polish Civil Code as well as to art. 81 par. 1 and 2 of the Copyright and Related Rights Act of 4th February 1994 which sets general legal frameworks for image rights in Poland. Abovementioned provisions of the Sport Act grants the Polish sports unions and the Polish Olympic Committee with the exclusive right to use, in order to their business goals, image of the athletes wearing, respectively, the Polish national team outfit or the Olympic team outfit. Specific legal provisions functioning in relation to the professional athletes’ image were also the subject of the case law of the Supreme Court. Of key importance for the interpretation of art. 14 paragraphs 1-3 of the Sports Act has a Supreme Court judgment of 16th December 2009, I CSK 160/09, which was issued on the basis of art. 33 paragraph 1 and 2 of the repealed Qualified Sport Act. For issues of athletes image usage not without significance is the fact that professional athletes usually have the status of a commonly known persons. In the light of art. 81 par. 2 of Sports Act disseminating the image of an athlete who is commonly known person as well, does not require the consent of such a person, provided that the image has been made in connection with the performance of public functions, in particular social or professional ones. Regarding to the issue of entities authorized to disseminating athletes image there is considerable diversity. Depending on the factual situation, except of an athlete itself, such entitled entity might become the Polish Olympic Committee, the Polish sport union, sport club or organization for collective management of rights of athletes. Having regard to the multidimensional issue of the athletes' image, and bearing in mind how common practice concluding of the marketing contracts concerning image rights has become, it should be postulated that observable changes concerning issue in question, shall be made towards meeting the needs espoused by the market. Keywords: sports law, image rights, athletes’ image rights, image rights commercialization, marketing in sports [1] mgr Krzysztof M. Westfal, e-mail: k.m.westfal@gmail.com